Analisa teknologi dan keekonomian de-dieselisasi PLTD Merawangg menjadi Pembangkit Tenaga Angin / Tenaga Surya di Pulau Bangka, Bangka Belitung - Arya Bima Aji Kusuma ST; Rinaldy Dalimi (Jurnal Impresi Indonesia, 2025)
PLTD Merawangg in Bangka Island still relies on expensive diesel fuel, resulting in high operational costs carbon emissions. The Indonesian government initiated a dedieselization program to replace or hybridize diesel power plants with renewable energy sources such as solar and wind to reduce energy costs (COE) and emissions. This study aims to identify the most optimal and economical hybrid power plant configuration through simulation of on-grid and off-grid scenarios with varying renewable energy proportions. The method used is quantitative simulation based on electricity demand data, renewable energy potential, and equipment costs. The results show that a hybrid configuration of 75% solar PV hybrid 25% with diesel produces the lowest COE of 1.660 rupiah/kWh, significantly lower than the current PLTD COE and the Bangka Belitung provincial standard. This scenario is economically feasible with positive NPV values meeting investment criteria. Conversely, wind turbine configurations yield higher COE due to wind variability and expensive technology costs. The study’s implications support the dedieselization program by recommending solar-based hybrid configurations as an efficient and environmentally friendly solution for island regions.